Keeping Warm in Subtropical Winter. When Everyday Life Disrupts the Concept of Hyper-Conditioned Environments in Chongqing (Southwest China) - Madlen Kobi (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The practice of regulation of indoor climates has spread globally with the rise of modern architecture and has cemented the idea of an air-conditioned indoors as opposed to a non-controllable outdoors. The ethnographic data discussed here from the metropolis of Chongqing (southwest China) presents a more nuanced picture and encourages scrutiny of the notion of “hyper-conditioned environments”. Local thermal practices are not clear-cut along the lines of indoors and outdoors; rather, everyday life takes place in a range of adjoined microclimates. Building upon the centrality of the body for perceiving thermal differences, this paper analyses the interaction of climate, landscape and architecture in an era where hyper-conditioned environments are taken for granted. The paper develops an argument for more place-based studies on how conditioning is conceived in specific contexts. In a highly urbanized setting such as Chongqing, it is not only local climatic characteristics (e.g. little wind or high humidity) that affect architecture. Further, the national political economy that promulgates poorly insulated houses or residential customs such as ventilation interfere in the warming or cooling of bodies. This paper aims to sensitize architects to conceptualizing buildings not as detached and controllable entities, but as part of urban climatic landscapes.